Jumlah Talak Akibat Jatuhnya Bain Sughra Menurut Fikih dan Kompilasi Hukum Islam - Imamul Muttaqin (Program Studi Hukum Keluarga Islam STAIN Mandailing Natal, 2020)
Talak bain sughra is a divorce that falls as a result of the husband not referring to the wife in the period of iddah or the husband divorces a wife he has never touched, the problem that arises is, what is the remaining amount of divorce for the husband, whether due to the sain bain divorce the number of divorces continues so that the husband has two divorces again or the number of divorce back to the beginning means the husband has the number of divorce that is three times the divorce